Rancang Bangun Sistem Informasi Manajemen Seleksi Penerimaan Mahasiswa Baru Universitas Lancang Kuning - Yogo Turnandes Nandes*; Zamzami Zamzami; Syahtriatna D; Ahmad Zamsuri; Vebby Vebby (Jurnal Karya Ilmiah Multidisiplin (JURKIM), 2023)
Information System for New Student Registration or now called Web-based New Student Admissions (PMB) at Lancang Kuning University, Pekanbaru. Due to the rapid advancement of technology, everything from everyday life to education, which requires timely and accurate information, has benefited. Processing new student registration information online aims to produce effective and efficient performance, get information more easily and don't have to waste a lot of money that has to be spent. It is hoped that this online service will make it easier for the general public to obtain information. This system can be more effective in spending costs, time, and energy, so it is effective in achieving goals.